Promises and Pitfalls of Calcineurin Inhibitors in COVID-19: A Systematic Review and Meta-analysis of Controlled Trials - Heydari, Behrooz; Sahebnasagh, Adeleh; Omrani, Mohammad Ali; Azimi, Saeed; Dehghani, Mohammad Hossein; Salehi-Abargouei, Amin; Farman, Farnoosh; Saghafi, Fatemeh (Current Medicinal Chemistry, 2024)
Objective: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes a violent attack on the body that leads to multi-organ failure and death in COVID-19 patients. The aim of this study was to systematically review the existing literature on the potential benefits of calcineurin inhibitors (CIs) as anti-vascular endothelial growth factor (VEGF) agents in improving the clinical outcomes of COVID-19 patients. Methods: We searched various databases, including PubMed, Scopus, ISI Web of Science, Google Scholar, Cochrane databases, and ClinicalTrials.gov from 31st December, 2019, to 3rd February, 2023, for relevant controlled trials. The quality of the evidence was assessed using the Cochrane Collaboration tool. Comprehensive Meta-Analysis Software was used for the statistical analyses using a random-effects model. Results: Three trials enrolling 293 participants were reviewed in the present systematic review and meta-analysis. The results showed CIs to lead to a significant reduction in mortality rate [risk ratio (RR): 0.598, 95% CI: 0.404-0.885, P-value = 0.010] with a low between-study heterogeneity (Cochrane Q test: I2 = 0.000%, P-value = 0.371). Pooled analysis of two studies (84 patients) illustrated that CIs could not significantly increase the rate of hospital discharge (RR: 1.161, 95% CI: 0.764-1.764, P-value = 0.485) and heterogeneity was not significant (Cochrane Q test: I2 = 26.798%, P-value = 0.242). Conclusion: CIs are able to inhibit the virus nucleocapsid protein so that they can prevent replication and respiratory tract tissue damage caused by SARS-CoV-2. Based on the characteristics mentioned in detail, CIs can play a potential therapeutic role for COVID-19 patients.
Keywords: Calcineurin inhibitors